K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 9 2024

         Bài 1:

\(\dfrac{11}{2}x\) + 1 = \(\dfrac{1}{3}x-\dfrac{1}{4}\)

\(\dfrac{11}{2}\)\(x\) - \(\dfrac{1}{3}\)\(x\) = - \(\dfrac{1}{4}\) - 1

-(\(\dfrac{33}{6}\) + \(\dfrac{2}{6}\))\(x\) = - \(\dfrac{5}{4}\)

\(\dfrac{35}{6}\)\(x\) = - \(\dfrac{5}{4}\)

  \(x=-\dfrac{5}{4}\) : (- \(\dfrac{35}{6}\))

 \(x\) = \(\dfrac{3}{14}\)

Vậy \(x=\dfrac{3}{14}\)

 

 

27 tháng 9 2024

Bài 2: 2\(x\) - \(\dfrac{2}{3}\) - 7\(x\) = \(\dfrac{3}{2}\) - 1

         2\(x\) - 7\(x\) = \(\dfrac{3}{2}\) - 1 + \(\dfrac{2}{3}\)

         - 5\(x\)    = \(\dfrac{9}{6}\) - \(\dfrac{6}{6}\) + \(\dfrac{4}{6}\) 

        - 5\(x\)    = \(\dfrac{7}{6}\)

           \(x\)    = \(\dfrac{7}{6}\) : (- 5) 

          \(x\)    = - \(\dfrac{7}{30}\)

Vậy \(x=-\dfrac{7}{30}\)

 

13 tháng 10 2021

a: \(\dfrac{x}{0.9}=\dfrac{5}{6}\)

\(\Leftrightarrow x=\dfrac{3}{4}\)

b: \(\dfrac{-6}{x}=\dfrac{9}{-15}\)

\(\Leftrightarrow x=10\)

c: \(\dfrac{\dfrac{14}{15}}{\dfrac{9}{10}}=\dfrac{x}{\dfrac{3}{7}}\)

\(\Leftrightarrow x=\dfrac{3}{7}\cdot\dfrac{14}{15}:\dfrac{9}{10}=\dfrac{2}{5}\cdot\dfrac{10}{9}=\dfrac{20}{45}=\dfrac{4}{9}\)

13 tháng 7 2019

a,  3^9:3^2=3^7

b,  (3/5)^15:(3/5)^10=(3/5)^5

c,  (5.3.3)^10.5^10 / (5.5.3)^10=5^10.3^10.3^10.5^10 / 5^10.5^10.3^10=5^20.3^20 / 5^20.3^10=3^10

17 tháng 7 2019

1) \(\frac{25}{12}.x+\frac{11}{15}=\frac{9}{10}\)

=> \(\frac{25}{12}.x=\frac{9}{10}-\frac{11}{15}\)

=> \(\frac{25}{12}.x=\frac{1}{6}\)

=> \(x=\frac{1}{6}:\frac{25}{12}\)

=> \(x=\frac{2}{25}\)

Vậy \(x=\frac{2}{25}\).

3) \(\frac{29}{12}.\left[x\right]-\frac{5}{6}=\frac{3}{8}\)

=> \(\frac{29}{12}.\left[x\right]=\frac{3}{8}+\frac{5}{6}\)

=> \(\frac{29}{12}.x=\frac{29}{24}\)

=> \(x=\frac{29}{24}:\frac{29}{12}\)

=> \(x=\frac{1}{2}\)

Vậy \(x=\frac{1}{2}\).

4) \(\left[4x+\frac{3}{4}\right]-\frac{5}{4}=2\)

=> \(\left[4x+\frac{3}{4}\right]=2+\frac{5}{4}\)

=> \(4x+\frac{3}{4}=\frac{13}{4}\)

=> \(4x=\frac{13}{4}-\frac{3}{4}\)

=> \(4x=\frac{5}{2}\)

=> \(x=\frac{5}{2}:4\)

=> \(x=\frac{5}{8}\)

Vậy \(x=\frac{5}{8}\).

5) 2x + 2x+3 = 144

⇔ 2x + 2x . 23 = 144

⇔ 2x . (1 + 23) = 144

⇔ 2x . 9 = 144

⇔ 2x = 144 : 9

⇔ 2x = 16

⇔ 2x = 24

=> x = 4

Vậy x = 4.

Chúc bạn học tốt!

1 tháng 10 2017

a. \(5.\left(x-2\right)+3.\left(x-2\right)=0\)

\(\Rightarrow8.\left(x-2\right)=0\)

\(\Rightarrow x-2=0:8\)

\(\Rightarrow x-2=0\)

\(\Rightarrow x=2\)

Vậy...

b. \(\dfrac{2}{3}+\dfrac{5}{2}:x=\dfrac{2}{4}\)

\(\Rightarrow\dfrac{5}{2}:x=\dfrac{2}{4}-\dfrac{2}{3}\)

\(\Rightarrow\dfrac{5}{2}:x=\dfrac{-1}{6}\)

\(\Rightarrow x=\dfrac{5}{2}:\dfrac{-1}{6}=-15\)

Vậy...

c. \(2.\left(x-\dfrac{1}{7}\right)=0\)

\(\Rightarrow x-\dfrac{1}{7}=0:2\)

\(\Rightarrow x-\dfrac{1}{7}=0\)

\(\Rightarrow x=\dfrac{1}{7}\)

Vậy...

d. \(\dfrac{11}{20}-\left(\dfrac{2}{5}+x\right)=\dfrac{2}{3}\)

\(\Rightarrow\dfrac{2}{5}+x=\dfrac{11}{12}:\dfrac{2}{3}\)

\(\Rightarrow\dfrac{2}{5}+x=\dfrac{1}{4}\)

\(\Rightarrow x=\dfrac{1}{4}-\dfrac{2}{5}=\dfrac{-3}{20}\)

Vậy...

e. \(\dfrac{3}{4}+\dfrac{1}{4}:x=\dfrac{2}{5}\)

\(\Rightarrow\dfrac{1}{4}:x=\dfrac{2}{5}-\dfrac{3}{4}\)

\(\Rightarrow\dfrac{1}{4}:x=\dfrac{-7}{20}\)

\(\Rightarrow x=\dfrac{1}{4}:\dfrac{-7}{20}=\dfrac{-5}{7}\)

Vậy...

g. \(\dfrac{2}{3}x+\dfrac{5}{7}=\dfrac{3}{10}\)

\(\Rightarrow\dfrac{2}{3}x=\dfrac{3}{10}-\dfrac{5}{7}\)

\(\Rightarrow\dfrac{2}{3}x=\dfrac{-29}{70}\)

\(\Rightarrow x=\dfrac{-29}{70}:\dfrac{2}{3}=\dfrac{-87}{140}\)

Vậy...

15 tháng 9 2019

Tìm x nhé

a: 2x-3/2+3/4=-4

=>2x-3/4=-4

=>2x=-13/4

hay x=-13/8

b: \(\left(-\dfrac{2}{3}x-\dfrac{3}{5}\right)\cdot\left(\dfrac{-3}{2}-\dfrac{10}{3}\right)=\dfrac{2}{5}\)

\(\Leftrightarrow-\dfrac{2}{3}x-\dfrac{3}{5}=\dfrac{2}{5}:\dfrac{-29}{6}=\dfrac{-2}{5}\cdot\dfrac{6}{29}=\dfrac{-12}{145}\)

=>2/3x+3/5=12/145

=>2/3x=-15/29

hay x=-45/58

c: \(\dfrac{x}{2}-\left(\dfrac{3}{5}x-\dfrac{13}{5}\right)=-\left(\dfrac{7}{10}x+\dfrac{7}{5}\right)\)

=>1/2x-3/5x+13/5=-7/10x-7/5

=>-1/10x+7/10x=-7/5-13/5

=>3/5x=-2

hay x=-2:3/5=-10/3

a,  \(\frac{\left(5-2x\right)}{3}=\frac{\left(4x-1\right)}{-5}\)

\(\Leftrightarrow-5(5-2x)=3\left(4x-1\right)\)

\(\Leftrightarrow10x-25=12x-3\)

\(\Leftrightarrow10x-12x=25-3\)

\(\Leftrightarrow-2x=22\)

\(\Leftrightarrow x=-11\)

b,  \(\frac{\left(12-3x\right)}{32}=\frac{6}{\left(4-x\right)}\)

\(\Leftrightarrow\frac{3\left(4-x\right)}{32}=\frac{6}{\left(4-x\right)}\)

\(\Leftrightarrow3(4-x)\left(4-x\right)=32.6\)

\(\Leftrightarrow(4-x)\left(4-x\right)=32.2\)

\(\Leftrightarrow(4-x)^2=64\)

\(\Leftrightarrow\orbr{\begin{cases}4-x=8\\4-x=-8\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=-4\\x=12\end{cases}}\)

c,  \(\frac{\left(10-2x\right)}{6}=\frac{27}{\left(5-x\right)}\)

\(\Leftrightarrow\frac{2\left(5-x\right)}{6}=\frac{27}{\left(5-x\right)}\)

\(\Leftrightarrow2(5-x)\left(5-x\right)=27.6\)

\(\Leftrightarrow(5-x)\left(5-x\right)=27.3\)

\(\Leftrightarrow(5-x)^2=81\)

\(\Leftrightarrow\orbr{\begin{cases}5-x=9\\5-x=-9\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=-4\\x=14\end{cases}}\)

1 tháng 10 2020

a, \(\frac{5-2x}{3}=\frac{4x-1}{-5}\Leftrightarrow-25+10x=12x-3\Leftrightarrow-22-2x=0\Leftrightarrow x=-11\)

b, \(\frac{12-3x}{32}=\frac{6}{4-x}\Leftrightarrow\frac{12-3x}{32}=\frac{18}{12-3x}\)

\(\Leftrightarrow\left(12-3x\right)^2=576\Leftrightarrow12-3x=\pm2\)\(\Leftrightarrow\orbr{\begin{cases}x=\frac{10}{3}\\x=\frac{14}{3}\end{cases}}\)

c, \(\frac{10-2x}{6}=\frac{27}{5-x}\Leftrightarrow\frac{10-2x}{6}=\frac{54}{10-2x}\)

\(\Leftrightarrow\left(10-2x\right)^2=324\Leftrightarrow10-2x=\pm18\)\(\Leftrightarrow\orbr{\begin{cases}x=14\\x=-4\end{cases}}\)

Bài 1: 

1: 7/20-|x+2/5|=10/21

=>|x+2/5|=-53/420(vô lý)

2: \(\left|\dfrac{3}{7}-x\right|-\left(-\dfrac{2}{3}\right)=1+\dfrac{1}{2}\)

\(\Leftrightarrow\left|x-\dfrac{3}{7}\right|=\dfrac{3}{2}-\dfrac{2}{3}=\dfrac{5}{6}\)

=>x-3/7=5/6 hoặc x-3/7=-5/6

=>x=53/42 hoặc x=-17/42

23 tháng 6 2018

\(a,\frac{-3}{2}-2x+\frac{3}{4}=-1\)

\(\frac{-3}{2}-2x=-1-\frac{3}{4}\)

\(\frac{-3}{2}-2x=\frac{-7}{4}\)

\(2x=\frac{-7}{4}+\frac{-3}{2}\)

\(2x=\frac{-13}{4}\)

\(x=\frac{-13}{4}:2\)

\(x=\frac{-13}{4}.\frac{1}{2}\)

\(x=\frac{-13}{8}\)